Equation-of-state exchange parameters of poly(methyl methacrylate) with some aliphatic esters - Cankurtaran, O; Saraç, A; Yilmaz, F (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
The retention diagram of poly(methyl methacrylate) with n-nonane and ethyl acetate was obtained at temperatures between 80 degreesC and 200 degreesC by gas chromatography. Thermodynamical equilibration was reached beyond 160 degreesC. The parameters of hard-core polymer-solvent interaction, chi (infinity)(t), effective exchange energy, (X) over bar (12) , exchange enthalpy, X-12 and exchange entropy, Q(12) were determined for the polymer with solvents such as methyl acetate, ethyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, tert-butyl acetate and isoamyl acetate at temperatures between 175 degreesC and 195 degreesC. It was observed that the value of parameter chi (infinity)(t) decrease, i.e. the solubility of polymer increase as carbon number and branching of the alkyl group in the solvent increase at studied temperatures. The polymer exhibits exothermic solubility in lower molecular weight esters such as methyl acetate and ethyl acetate but it exhibits endothermic solubility as the molecular weight of the ester increase. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: poly(methyl methacrylate); equation of state; solubility; interaction parameter; exchange parameter; INVERSE GAS-CHROMATOGRAPHY; ENTROPY PARAMETERS; INTRINSIC-VISCOSITY; POLY(DIMETHYL SILOXANE); ENTHALPY; Polymer Science